Role of Nigerian Public Libraries in Reaching Rural Communities with Sustainable Development Goals (SDGs) - Adepoju, Folasade; Akobe, Oluwatosin Daniel (Access: An International Journal of Nepal Library Association, 2023)
Libraries and information centers occupy a central place in the provision of information services to urban and rural dwellers. The public library provides information, inculcates ideas, and develops knowledge that is so essential to functioning successfully in today’s information and knowledge-based society. The presence of libraries in different environments and the target they serve indicates that libraries have significant roles to play in supporting sustainable development goals whose actors and targets are also diversified. Libraries can support SDGs through the following activities: supporting the research process, ensuring research visibility, and reducing research anxiety of patrons among others. The activities of librarians go beyond listing to that of taking charge and delivering to the patron’s relevant information to drive and actualize the sustainable developmental goals this is also viewed as library inclusiveness. This paper articulated some roles that public libraries can play in reaching rural communities with sustainable development goal. Also, some factors that pose a challenge to rural communities with sustainable development goals were also identified.